Fodder cum grain dual harvests from rice (Oryza sativa) for enhanced productivity in Andaman’s - GANGAIAH, B (The Indian Journal of Agricultural Sciences, 2021)
An experiment was conducted during kharif 2016-17 to assess the impact of fodder harvest on grain production and system productivity of long duration photosensitive rice C-14-8. For this, five fodder harvest treatments, FHTs no fodder harvest (FH) control, FH at 30, 45, 60 and 75 days after transplanting (DAT) of rice were evaluated in Randomised Complete Block Design with four replications. The results revealed that 75 DAT FHT has produced significantly higher dry fodder and crude protein yields (6.30 and 0.538 t/ha), whereas 30 and 45 DAT FHTs has higher grain yields. However, the system productivity measured as rice equivalent yield and net income indicated that FH at 75 DAT was promising (4.23 t/ha and ` 19088/ha). Lodging in grain alone producing crop (95%) was reduced to 24% by taking FH at 75 DAT. Thus, the study establishes fodder cum grain production system of rice as a potential solution to augment fodder shortages while enhancing the grain production from ratoon owing to reduced lodging.